Nanosheet heterostructure based on alkali etching, preparation method thereof and application of nanosheet heterostructure in electrochemical oxygen evolution reaction

By adopting a heterostructure of nickel, iron, cobalt, aluminum layered bimetallic hydroxide nanosheets based on alkali etching in the electrolytic water catalyst, the problems of high overpotential and high power consumption in the oxygen evolution reaction are solved, and a low-cost and high catalytic activity catalyst is achieved, reducing the cost of hydrogen production.

CN119800412AActive Publication Date: 2025-04-11SHANDONG NORMAL UNIV

Patent Information

Application Number
CN202510227196.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-04-11
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

Existing electrolytic catalysts exhibit high overpotential and high power consumption in oxygen evolution reactions, resulting in high hydrogen production costs and high cost and scarcity of precious metal-based catalysts, limiting their large-scale applications.

Method used

The heterostructure of nickel, iron, cobalt, aluminum layered bimetallic hydroxide nanosheets based on alkali etching is used as a catalyst. Through element doping and alkali etching methods, the electronic structure and surface properties of the catalyst are optimized and its catalytic activity is improved.

Benefits of technology

A low-cost, high-catalytic activity oxygen evolution reaction catalyst is achieved, with lower overpotential and higher current density, reducing the cost of hydrogen production and simplifying the preparation process of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800412A_ABST
    Figure CN119800412A_ABST
Patent Text Reader

Abstract

The invention discloses a nanosheet heterostructure based on alkali etching, a preparation method of the nanosheet heterostructure and application of the nanosheet heterostructure in an electrochemical oxygen evolution reaction, and belongs to the technical field of water electrolysis catalytic materials. The preparation method comprises the following steps: S1, preparation of a nickel-iron-cobalt-aluminum layered double-metal hydroxide precursor: weighing metal salt, adding water, adding urea, violently stirring, transferring the obtained product into a polytetrafluoroethylene lining, sealing, putting into a stainless steel high-pressure kettle, and heating for reaction; taking out after cooling, and cleaning and drying the obtained product; and S2, preparing the nickel-iron-cobalt-aluminum layered double-metal hydroxide: etching by using an alkali solution. The nanosheet heterostructure is etched by alkali, so that the nanosheet structure is lighter and thinner, the specific surface area of the catalyst and the number of active sites are increased, reaction substances are easier to adsorb and diffuse, chemical reactions such as oxygen evolution reaction (OER) are accelerated, and the catalytic activity of the catalyst is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytic water catalytic materials, and in particular relates to a nanosheet heterostructure based on alkali etching, a preparation method thereof and an application thereof in an electrochemical oxygen evolution reaction. Background Art

[0002] The burning of fossil fuels will release a large amount of greenhouse gases, which will cause environmental pollution and threaten people's health. The development of renewable energy can reduce the use of fossil fuels. Clean energy such as solar energy and wind energy has the advantage of being inexhaustible and can effectively reduce greenhouse gas emissions and protect the environment. Hydrogen energy is regarded as a green alternative to fossil fuels due to its high calorific value and pollution-free characteristics.

[0003] With the rapid development of renewable energy (such as wind power and solar energy), the use of excess electricity to electrolyze water to produce hydrogen has become the main way to achieve green hydrogen energy. The water electrolysis reaction is divided into the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. However, due to the slow kinetics of the oxygen evolution reaction, water electrolysis requires a large reaction overpotential, which leads to excessive power consumption and high hydrogen production costs. Precious metal-based catalysts such as IrO2 and RuO2 show excellent OER activity, but their high cost and scarcity limit their large-scale application. Therefore. It is urgent to develop low-cost, high-catalytic activity oxygen evolution reaction catalysts as alternatives. Among transition metals, nickel-iron elements and layered double hydroxides have shown great potential in oxygen evolution electrocatalytic performance due to their unique layered structure. However, their poor intrinsic conductivity and low basal catalytic activity restrict their electrocatalytic performance.

[0004] Nanosheet heterostructures can be rationally designed and combined to optimize the electronic structure and surface properties of the catalyst, thereby improving its catalytic activity for the oxygen evolution reaction (OER). However, the preparation of nanosheet heterostructures usually requires more complex synthesis methods and process conditions, and it is difficult to precisely control the composition, morphology, and size of the heterostructure, which may lead to certain differences and uncertainties in the performance of the catalyst.

[0005] The preparation of nanosheet heterostructures by alkaline etching can create a porous structure on the surface of the nanosheet, greatly increasing the specific surface area and the number of active sites of the catalyst, thereby optimizing the microstructure of the nanosheet. This makes it easier for the reactants to adsorb and diffuse, accelerating chemical reactions such as the oxygen evolution reaction (OER), thereby improving the catalytic activity of the catalyst.

[0006] The preparation of nanosheet heterostructures usually requires more complex synthesis methods and process conditions, and it is difficult to accurately control the composition, morphology, and size of the heterostructures, which may lead to certain differences and uncertainties in the performance of the catalyst. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention provides a nanosheet heterostructure based on alkali etching, a preparation method thereof and an application in an electrochemical oxygen evolution reaction. The present invention adopts the following technical solutions:

[0008] In one aspect, the present invention provides a method for preparing a nanosheet heterostructure based on alkali etching, comprising the following steps:

[0009] S1, preparation of nickel-iron-cobalt-aluminum layered double hydroxide precursor: weighing metal salts, the metal salts including cobalt salt, iron salt, nickel salt and aluminum salt; adding water, then adding urea, after vigorous stirring, transferring the obtained product to a polytetrafluoroethylene liner, sealing it and placing it in a stainless steel autoclave, heating for reaction; taking it out after cooling, and washing and drying the obtained product;

[0010] S2, Preparation of nickel-iron-cobalt-aluminum layered double hydroxide: etching with alkaline solution.

[0011] Preferably, in step S1, the metal salt is a metal chloride, nitrate, sulfate or phosphate.

[0012] Preferably, in step S1, the cobalt salt is cobalt chloride hexahydrate, the aluminum salt is aluminum chloride hexahydrate, the iron salt is ferric chloride hexahydrate, and the nickel salt is nickel chloride hexahydrate.

[0013] Preferably, in step S1, the relatively weak alkalinity of urea is utilized, and the precursor is relatively easy to synthesize under this condition.

[0014] Preferably, in step S1, the reaction temperature is 90°C to 120°C.

[0015] Preferably, in step S1, when preparing the precursor, the added reactants CoCl2·6H2O and AlCl3·6H2O account for 90% in total, and NiCl2·6H2O and FeCl3·6H2O account for 10% in total.

[0016] Furthermore, in step S1, the ratio of CoCl2·6H2O to AlCl3·6H2O is 3:1, and the ratio of NiCl2·6H2O to FeCl3·6H2O is 3:1.

[0017] Preferably, in step S2, the alkaline solution is a strong alkaline solution selected from potassium hydroxide or sodium hydroxide. Since aluminum is amphoteric, it can form tetrahydroxyaluminate with a strong base, dissolve in water, and use the strong base to etch aluminum ions.

[0018] Preferably, in step S2, the concentration of the alkaline solution is 8M, and etching is performed at room temperature.

[0019] Preferably, in step S2, the alkaline etching is performed at room temperature.

[0020] Due to the amphoteric nature of aluminum ions, they can generate tetrahydroxyaluminum ions when the alkali concentration is high. Therefore, aluminum ions and etching are both to make aluminum ions in the second step of etching, freeing up sites, which is conducive to the doping of elements such as Ni, Fe, and Co that are more likely to form active sites into the catalyst. In essence, it is to create more active sites.

[0021] In a second aspect, the present invention also provides a product obtained by a method for preparing a nanosheet heterostructure based on alkali etching.

[0022] In a third aspect, the present invention also provides an application of a product obtained by a method for preparing a nanosheet heterostructure based on alkali etching in an electrochemical oxygen evolution reaction, wherein the product is used as a catalyst in the electrochemical oxygen evolution reaction.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) Based on layered metal hydroxide (LDHs) materials, the present invention uses element doping to synthesize a water electrolysis catalyst with better performance. Experimental comparison shows that it has a lower overpotential and a higher current density (LSV).

[0025] (2) The present invention provides a nanosheet heterostructure prepared by an alkali etching method, which has a unique layered structure of a layered metal hydroxide and can provide a larger specific surface area. This means that there are more active sites available for adsorbing reactants (such as water molecules and ions) to promote the occurrence of water electrolysis reaction.

[0026] By alkali etching the nanosheet heterostructure, the nanosheet structure is made thinner and lighter, which increases the specific surface area and the number of active sites of the catalyst, making the reactants easier to adsorb and diffuse, accelerating chemical reactions such as the oxygen evolution reaction (OER), and improving the catalytic activity of the catalyst.

[0027] (3) The present invention can reduce the activation energy of the water electrolysis reaction to a certain extent by doping different metal ions and utilizing the synergistic effect between ions.

[0028] (4) The preparation process of the present invention is relatively simple, does not require complicated equipment and operation steps, is convenient for laboratory research and industrial production, and can quickly prepare nanosheet heterostructures. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0030] Figure 1The XRD diffraction image of the 10% alkali-etched nickel-iron-cobalt-aluminum layered double hydroxide material prepared in Example 1 of Experimental Example 1;

[0031] Figure 2 The scanning electron microscope image and the transmission electron microscope image of the 10% alkali-etched nickel-iron-cobalt-aluminum layered double hydroxide material prepared in Example 1 in Experimental Example 1 are shown, wherein (a) is a scanning electron microscope image and (b) is a transmission electron microscope image;

[0032] Figure 3 This is a comparison diagram of the LSV properties of the samples of Examples 1 to 5 in Experimental Example 2;

[0033] Figure 4 It is a comparison chart of CV properties of samples of Examples 1 to 5 in Experimental Example 2;

[0034] Figure 5 This is the LSV property diagram of the samples of Example 6, Comparative Example 1, Comparative Example 2 and Example 1 in Experimental Example 2. DETAILED DESCRIPTION

[0035] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0036] Terminology explanation:

[0037] Nanosheet heterostructure: refers to a material system with unique properties and structure formed by combining two or more nanosheets of different materials in a specific way. The advantages of each component material complement and synergize each other, making the heterostructure have better comprehensive properties than a single material. It can be used as an efficient catalyst for catalysis of chemical reactions.

[0038] Alkali etching: It is a material surface treatment technology that uses alkaline solution to react with the material, selectively dissolves part of it, and changes the surface morphology, structure or performance.

[0039] Layered metal hydroxides (LDHs): generally composed of divalent and trivalent metal hydroxides to form octahedral two-dimensional layered plates, with metal ions located at the center of the octahedron, surrounded by hydroxide ions, and the layers are connected by sharing edges or corners to form a two-dimensional plane. The structural characteristics of LDHs allow their interlayer anions to be exchanged with various anions. This property can be used to adjust the type of interlayer anions to synthesize different types of LDHs and give them different properties, thereby obtaining a new class of materials with different functions.

[0040] Example 1

[0041] The first step is the preparation of 10% nickel-iron-cobalt-aluminum layered double hydroxide precursor: CoCl2·6H2O (0.81mmol), AlCl3·6H2O (0.27mmol), FeCl3·6H2O (0.03mmol), and NiCl2·6H2O (0.09mmol) are weighed in a beaker using a 1 / 10,000 balance. Note that the iron salt is weighed last and added last. Add 80ml of deionized water, then add 3.2mmol of urea (0.192g), and stir vigorously for 30min. After stirring for 30min, transfer the solution to a 100mL polytetrafluoroethylene liner, seal it, place it in a stainless steel autoclave, and react at 100℃ for 24h. After cooling to room temperature, take out the autoclave, and then wash the obtained product several times with deionized water and anhydrous ethanol, and finally dry it in a vacuum drying oven.

[0042] Step 2: Preparation of nickel-iron-cobalt-aluminum layered double hydroxide (main product) etched with 10% alkali: etch with 8M NaOH at room temperature. Specific steps: take 30 mg of sample in a beaker, add 10 ml of water and stir, add the largest magnetic particle, stir evenly, and then mix with 30 ml of NaOH solution, a total of 40 ml of solution, with a total concentration of 8M NaOH, and etch vigorously at room temperature for 12 hours.

[0043] Example 2

[0044] The first step is the preparation of 10% nickel cobalt aluminum layered double hydroxide precursor (NiCoAl-e 10% Ni90% CoAl): NiCl2·6H2O (0.12mmol) AlCl3·6H2O (0.27mmol), CoCl2·6H2O (0.81mmol), in a beaker, add 80ml of deionized water, then add 3.2mmol of urea (0.192g), and stir vigorously for 30min. After stirring for 30min, the solution was transferred to a 100mL polytetrafluoroethylene liner, sealed and placed in a stainless steel autoclave, and reacted at 100°C for 24h. After cooling to room temperature, the autoclave was taken out, and the obtained product was washed several times with deionized water and anhydrous ethanol, and finally dried in a vacuum drying oven.

[0045] Step 2: Preparation of nickel-cobalt-aluminum layered double hydroxides by 10% alkaline etching: Etching with 8M NaOH at room temperature. Specific steps: Take 30 mg of sample in a beaker, add 10 ml of water and stir, add the largest magnet, stir evenly, and then mix with 30 ml of NaOH solution, a total of 40 ml of solution, with a total concentration of 8M NaOH, and etch vigorously at room temperature for 12 hours.

[0046] Example 3

[0047] The first step is the preparation of 10% iron-cobalt-aluminum layered double hydroxide precursor (FeCoAl-e 10%Fe90%CoAl): FeCl3·6H2O (0.12mmol), AlCl3·6H2O (0.27mmol), CoCl2·6H2O (0.81mmol), in a beaker, add 80ml of deionized water, and then add 3.2mmol of urea (0.192g), and stir vigorously for 30min. After stirring for 30min, the solution was transferred to a 100mL polytetrafluoroethylene liner, sealed and placed in a stainless steel autoclave, and reacted at 100°C for 24h. After cooling to room temperature, the autoclave was taken out, and the obtained product was washed several times with deionized water and anhydrous ethanol, and finally dried in a vacuum drying oven.

[0048] Step 2: Preparation of iron-cobalt-aluminum layered double hydroxides etched with 10% alkali: Etching with 8M NaOH at room temperature. Specific steps: Take 30 mg of sample in a beaker, add 10 ml of water and stir, add the largest magnet, stir evenly, and then mix with 30 ml of NaOH solution, a total of 40 ml of solution, with a total concentration of 8M NaOH, and etch vigorously at room temperature for 12 hours.

[0049] Example 4

[0050] The first step is the preparation of 10% nickel-iron-aluminum layered double hydroxide precursor (NiFeAl-e 10% Ni Fe90% Al): AlCl3·6H2O (1.08mmol), FeCl3·6H2O (0.03mmol), NiCl2·6H2O (0.09mmol) are placed in a beaker, 80ml of deionized water is added, and 3.2mmol of urea (0.192g) is added, and the mixture is stirred vigorously for 30min. After stirring for 30min, the solution is transferred to a 100mL polytetrafluoroethylene liner, sealed, and placed in a stainless steel autoclave, and reacted at 100°C for 24h. After cooling to room temperature, the autoclave is taken out, and the obtained product is washed several times with deionized water and anhydrous ethanol, and finally dried in a vacuum drying oven.

[0051] Step 2: Preparation of nickel-iron-aluminum layered double hydroxides etched with 10% alkali: Etching with 8M NaOH at room temperature. Specific steps: Take 30 mg of sample in a beaker, add 10 ml of water and stir, add the largest magnet, stir evenly, and then mix with 30 ml of NaOH solution, a total of 40 ml of solution, with a total concentration of 8M NaOH, and etch vigorously at room temperature for 12 hours.

[0052] Example 5

[0053] The first step is the preparation of cobalt aluminum layered double hydroxide precursor (CoAl-e 75% Co 25% Al): take AlCl3·6H2O (0.3mmol) and CoCl2·6H2O (0.9mmol) in a beaker, add 80ml of deionized water, and then add 3.2mmol of urea (0.192g), and stir vigorously for 30min. After stirring for 30min, the solution was transferred to a 100mL polytetrafluoroethylene liner, sealed and placed in a stainless steel autoclave, and reacted at 100°C for 24h. After cooling to room temperature, the autoclave was taken out, and the obtained product was washed several times with deionized water and anhydrous ethanol, and finally dried in a vacuum drying oven.

[0054] Step 2: Preparation of alkaline-etched cobalt-aluminum layered double hydroxide: Etching with 8M NaOH at room temperature. Specific steps: Take 30 mg of sample in a beaker, add 10 ml of water and stir, add the largest magnet, stir evenly, and then mix with 30 ml of NaOH solution, a total of 40 ml of solution, with a total concentration of 8M NaOH, and etch vigorously at room temperature for 12 hours.

[0055] Embodiment 6,

[0056] The reaction temperature was changed to 200°C, and the other conditions were the same as in Example 1.

[0057] Comparative Example 1:

[0058] (1) Preparation and alkaline etching of 20% NiFe:CoAl layered double hydroxide:

[0059] Use a 1 / 10,000 balance to weigh CoCl2·6H2O (0.72mmol), AlCl3·6H2O (0.24mmol), FeCl3·6H2O (0.06mmol), and NiCl2·6H2O (0.18mmol) in a beaker. Note that the iron salt should be weighed last and added last. Add 80ml of deionized water, then add 3.2mmol of urea (0.192g), and stir vigorously for 30min. After stirring for 30min, transfer the solution to a 100mL polytetrafluoroethylene liner, seal it, place it in a stainless steel autoclave, and react at 100℃ for 24h. After cooling to room temperature, take out the autoclave, and then wash the obtained product with deionized water and anhydrous ethanol several times, and finally dry it in a vacuum drying oven.

[0060] Take 30 mg of sample in a beaker, add 10 ml of water and stir first, add the largest size magnet, stir evenly, and then mix with 30 ml of NaOH solution, a total of 40 ml of solution, with a total concentration of 8M NaOH, and etch vigorously at room temperature for 12 hours.

[0061] Comparative Example 2:

[0062] (1) Preparation and alkaline etching of 5% NiFe:CoAl layered double hydroxide:

[0063] Use a 1 / 10,000 balance to weigh CoCl2·6H2O (0.855mmol), AlCl3·6H2O (0.285mmol), FeCl3·6H2O (0.015mmol), and NiCl2·6H2O (0.045mmol) in a beaker. Note that the iron salt should be weighed last and added last. Add 80ml of deionized water, then add 3.2mmol of urea (0.192g), and stir vigorously for 30min. After stirring for 30min, transfer the solution to a 100mL polytetrafluoroethylene liner, seal it, place it in a stainless steel autoclave, and react at 100℃ for 24h. After cooling to room temperature, take out the autoclave, and then wash the obtained product with deionized water and anhydrous ethanol several times, and finally dry it in a vacuum drying oven.

[0064] Take 30 mg of sample in a beaker, add 10 ml of water and stir first, add the largest size magnet, stir evenly, and then mix with 30 ml of NaOH solution, a total of 40 ml of solution, with a total concentration of 8M NaOH, and etch vigorously at room temperature for 12 hours.

[0065] Test Example 1

[0066] Figure 1 The X-ray diffraction diagrams of the nanosheet heterostructure materials prepared in this embodiment and the comparative example show that CoO(OH) is detected, indicating that metal ions with higher valence states are generated, which means that there are more active sites.

[0067] Through transmission electron microscopy and scanning electron microscopy tests, such as Figure 2 As shown in (a) and (b), the nanosheet heterostructure prepared by the present invention is in sheet form and thin, so that it has better catalytic activity.

[0068] Test Example 2

[0069] The products prepared in the examples and comparative examples were used for water electrolysis test, and a typical three-electrode system was used to perform linear sweep voltammetry test on a Chenhua electrochemical workstation. The electrode coated with nanosheet heterostructure nanomaterials was used as the working electrode, the platinum electrode was used as the counter electrode, and the Hg / HgO electrode was used as the reference electrode. 1 mol / L potassium hydroxide was used as the electrolyte, and a glass electrolytic cell was used as the reaction device.

[0070] Comparison of LSV properties of samples from Example 1 to Example 5 Figure 3 As shown, the CV property comparison is Figure 4The electrochemical properties of the product of Example 1 of the present invention show that the main product 10% NiFe:CoAl is 10 mA cm -2 At a current density of 1.50 V vs. RHE, close to 240 mA cm -2 The current density, overpotential and maximum current density are all higher than those of the control sample, the properties are relatively excellent, and the catalytic efficiency is improved. The overpotential values ​​(mV) of NiFe:CoAl measured in Examples 1 to 6, Comparative Example 1 and Comparative Example 2 are shown in Table 1.

[0071] Table 1 NiFe:CoAl overpotential values ​​(mV) measured in Examples 1 to 6, Comparative Example 1 and Comparative Example 2

[0072]

[0073] The LSV properties of Example 6, Comparative Example 1 and Comparative Example 2 and the samples of Example 1 are as follows: Figure 5 As shown, it can be seen that the LSV curve measured in Example 6 is reduced. It is speculated that the reason may be that the temperature control is changed to 200°C. At high temperature, the layered double hydroxide morphology is uneven, and the sheet structure becomes thicker, which reduces the exposure of the edge active sites. Or the particles grow excessively and agglomerate, reducing the specific surface area, thereby reducing the active sites for catalytic reactions.

[0074] From the comparison between Comparative Example 1, Comparative Example 2 and Example 1, it can be seen that the LSV curves of the main product 20% NiFe:CoAl and the main product 5% NiFe:CoAl are lower than those of the main product 10% NiFe:CoAl, and the samples prepared by the ion ratios provided in Example 1 have better catalytic properties. 2+ and Co 2+ The ratio of Ni has a significant effect on the catalytic performance of the material (especially the electrolytic water performance). 2+ and Co 2+ The proportion of Ni will directly affect the electronic structure, number of active sites, conductivity and catalytic reaction kinetics of the material. The excellent amphoteric properties of Al are essential for alkaline etching. 2+ Provide active sites, Co 2+ Enhance electrical conductivity. The synergistic effect of the two improves catalytic efficiency. Fe3+ has rich redox properties and can enhance the redox ability of the material. The introduction of Fe3+ can adjust the electronic structure of layered double hydroxides and improve electrical conductivity. It is usually used as an auxiliary metal ion to combine with other metal ions (such as Ni 2 +, Co2+) to improve the catalytic performance. Aluminum ions have excellent amphoteric properties and play an important role in alkaline etching. They can form tetrahydroxyaluminate with strong bases and dissolve in water.

[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a nanosheet heterostructure based on alkaline etching, characterized in that: The steps include: S1, preparation of nickel-iron-cobalt-aluminum layered double hydroxide precursor: weighing metal salts, the metal salts including cobalt salt, iron salt, nickel salt and aluminum salt; adding water, then adding urea, after vigorous stirring, transferring the obtained product to a polytetrafluoroethylene liner, sealing it and placing it in a stainless steel autoclave, heating for reaction; taking it out after cooling, and washing and drying the obtained product; S2, preparation of nickel-iron-cobalt-aluminum layered double hydroxide: etching the nickel-iron-cobalt-aluminum layered double hydroxide precursor prepared in step S1 with an alkaline solution.

2. The method for preparing a nanosheet heterostructure based on alkali etching according to claim 1, characterized in that: In step S1, the metal salt is a metal chloride, nitrate, sulfate or phosphate.

3. The method for preparing a nanosheet heterostructure based on alkali etching according to claim 1, characterized in that: In step S1, the reaction temperature is 90°C to 120°C.

4. The method for preparing a nanosheet heterostructure based on alkali etching according to claim 1, characterized in that: In step S1, when the precursor is prepared, the cobalt salt is CoCl2·6H2O, the aluminum salt is AlCl3·6H2O, the iron salt is FeCl3·6H2O, and the nickel salt is NiCl2·6H2O; the added CoCl2·6H2O and AlCl3·6H2O account for 90% in total, and the added NiCl2·6H2O and FeCl3·6H2O account for 10% in total.

5. The method for preparing a nanosheet heterostructure based on alkali etching according to claim 4, characterized in that: In step S1, the ratio of CoCl2·6H2O to AlCl3·6H2O is 3:1, and the ratio of NiCl2·6H2O to FeCl3·6H2O is 3:

1.

6. The method for preparing a nanosheet heterostructure based on alkali etching according to claim 1, characterized in that: In step S2, the alkaline solution is a strong alkaline solution selected from potassium hydroxide or sodium hydroxide.

7. The method for preparing a nanosheet heterostructure based on alkali etching according to claim 1, characterized in that: In step S2, the concentration of the alkaline solution is 8M.

8. The method for preparing a nanosheet heterostructure based on alkali etching according to claim 1, characterized in that: In step S2, the alkaline etching is performed at room temperature.

9. A product obtained by a method for preparing a nanosheet heterostructure based on alkaline etching.

10. Use of the product obtained by the method for preparing nanosheet heterostructure based on alkali etching according to claim 9 in electrochemical oxygen evolution reaction.

Citation Information

Patent Citations

  • Preparation method of acid-etched Ni, Co, Fe ternary metal hydroxide oxygen evolution catalyst

    CN110586107A

  • Zinc-doped nickel-cobalt hydroxide ternary electrode material and application thereof as supercapacitor electrode

    CN113990672A

Cited By

  • Preparation method and application of Fe / Co / Ni-based ultrathin hydroxide or oxide nanosheet

    CN122377555A